Megaprosthesis anti-bacterial coatings: A comprehensive translational review. (1st March 2022) - Lex, Johnathan R; Koucheki, Robert; Stavropoulos, Nikolaos A; Michele, Joseph Di; Toor, Jay S; Tsoi, Kim; Ferguson, Peter C; Turcotte, Robert E; Papagelopoulos, Panayiotis J
Abstract: Periprosthetic joint infections (PJI) are catastrophic complications for patients with implanted megaprostheses and pose significant challenges in the management of orthopaedic oncology patients. Despite various preventative strategies, with the increasing rate of implanted orthopaedic prostheses, the number of PJIs may be increasing. PJIs are associated with a high rate of amputation. Therefore, novel strategies to combat bacterial colonization and biofilm formation are required. A promising strategy is the utilization of anti-bacterial coatings on megaprosthetic implants. In this translational review, a brief overview of the mechanism of bacterial colonization of implants and biofilm formation will be provided, followed by a discussion and classification of major anti-bacterial coatings currently in use and development. In addition, current in vitro outcomes, clinical significance, economic importance, evolutionary perspectives, and future directions of anti-bacterial coatings will also be discussed. Megaprosthetic anti-bacterial coating strategies will help reduce infection rates following the implantation of megaprostheses and would positively impact sarcoma care. Statement of significance: This review highlights the clinical challenges and a multitude of potential solutions to combating peri-prosthetic join infections in megaprotheses using anti-bacterial coatings. Reducing infection rates following the implantation of megaprostheses would have a major impact on sarcoma care and major trauma surgeries that require reconstruction of large skeletal defects. Graphical abstract: Image, graphical abstract